Causes of Sudden Cardiac Death on Autopsy Findings; a Four-Year Report - Rao, Dinesh; Sood, Divya; Pathak, P; Dongre, Sudhir. D (Archives of Academic Emergency Medicine, 2018)
Introduction: Incidence of sudden cardiac death (SCD) has been steadily increasing all over the world. While knowing the cause of SCD is one of the favorites of the physicians involved with these cases, it is very difficult and challenging task for the forensic physician. The present report is a prospective study regarding cause of SCDs on autopsy examination in four-year period, Bangalore, India. Methods: The present prospective study is based on autopsy observations, carried out for four-year period from 2008 to 2011, and analyzed for cause of SCDs. The cases were chosen as per the definition of sudden death and autopsied. The material was divided into natural and unnatural groups. Finally, on histopathology, gross examination, hospital details, circumstantial, and police reports the cause of death was inferred. Results: A total of 2449 autopsy was conducted of which 204 cases were due to SCD. The highest SCDs were reported in 50-60 years age group (62.24%; n-127), followed closely by the age group 60-69 (28.43%; n-58). Male to female ratio was around 10:1. The maximum number of deaths (n=78) was within few hours (6 hours) after the onset of signs and symptoms. In 24 (11.8%) cases major narrowing was noted in both the main coronaries, in 87 (42.6%) cases in the left anterior descending coronary artery (LAD), and in 18 (51.5%) cases in the right coronary artery (RCA). The major cardiac pathology resulting in sudden death was coronary artery disease (n-116; 56.86%) and myocardial infarction (n-104; 50.9%). most of the SCDs occurred in the place of residence (n-80; 39.2%) followed closely by death in hospital (n-49; 24.01%). Conclusion: Coronary occlusion was the major contributory cause of sudden death with cardiac origin and the highest number of deaths were reported in the age 50-59 years with male to female ratio of 10:1.